(untitled) (Sustainability in Debate, 2025)
An aspect that drew attention during the Bolsonaro administration (2019-2022) was his anti environmental rhetoric and policy. The central argument of this article is that by denying environmental sciences, Bolsonaro not only sought to dismantle an epistemic order based on mainstream scientific knowledge, but also to (de)construct a social order. To support this argument, we analysed his United Nations speeches from 2019 to 2022 using the notion of coproduction, as defined in Science and Technology Studies (STS) by Jasanoff (2004a, 2004b). The results show Bolsonaro’s attempt to produce new representations for the Amazon and new identities for the media, science, foreign countries and a “new Brazil.” We conclude that Bolsonaro sought to redefine the truth about environmental issues in the country to underpin and legitimise the dismantling of an institutional order of environmental protection built in Brazil over decades. Based on this conclusion, we critically reflect on the STS literature on the denialism of Jair Bolsonaro and his followers and on the concept of post-truth.